Малпасько тонэ: кырзанъёс / Николай Постников - Постников Николай Елисеевич (Удмуртия, 2010)
Экземпляры: Ч/з (20151221) / Инвентарный номер: 103348 / Цена: 100.00 / Сис.шифр: 85.319(2Рос.Удм) / Авт.знак: П 63 / ГРНТИ: 18.41 / ББК: 85.319